Isolated congenital urethrocutaneous fistula: Two case reports (Journal of Paediatric Surgeons of Bangladesh, 2024)
A common complication after hypospadias surgery is a urethrocuteneous fistula. But when it is congenital and present in isolated form, it becomes extremely uncommon and usually present in the paediatric age group and associated with hypospadias, chordee, or anorectal malformation. In this report, we are presenting 2 cases of uncircumcised boys with this rare entity of Isolated congenital anterior uretrocuteneous fistula, highlighting etiology, embryology, and surgical reconstructions for management.Journal of Paediatric Surgeons of Bangladesh (2019) Vol. 10 (1 & 2): 62-65